1989
DOI: 10.1007/bf00366847
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic data on doxycycline and its distribution in different biological fluids in female goats

Abstract: A pharmacokinetic study of doxycycline after intravenous administration at 5 mg/kg body weight in goats revealed that a concentration of greater than or equal to 0.5 microgram/ml was maintained for 5 min-2 h, 4-12 h, 2-12 h and 5 min-greater than 48 h in plasma, interstitial fluid, milk and urine respectively. The low t1/2 alpha of 0.73 +/- 0.11 h and high t1/2 beta of 16.63 +/- 1.58 h show that the drug is rapidly distributed but slowly eliminated from the body. The tissue:plasma concentration of 4.86 +/- 1.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 5 publications
3
25
2
Order By: Relevance
“…Other authors have reported values of the volume determined by the area method (V a ). In our study, V a was clearly lower than values obtained by Abd El-Aty et al (2004) in goats (6.48 ± 0.12 L/kg) and by Jha et al (1989) in lactating goats (9.78 ± 0.86 L/kg).…”
Section: Discussioncontrasting
confidence: 81%
See 4 more Smart Citations
“…Other authors have reported values of the volume determined by the area method (V a ). In our study, V a was clearly lower than values obtained by Abd El-Aty et al (2004) in goats (6.48 ± 0.12 L/kg) and by Jha et al (1989) in lactating goats (9.78 ± 0.86 L/kg).…”
Section: Discussioncontrasting
confidence: 81%
“…Our values were lower than those calculated in goats with mature ruminal function (11.83 ± 0.67 mL/kg/min) (Abd El-Aty et al, 2004). The discrepancies between values calculated for pharmacokinetic parameters may be attributed to the animal species, the drug formulation employed, the age, size or sex of the animals, to differences in fatty tissue deposits between animal species or breeds, or even to inter-individual variations (Riond et al, 1989;Jha et al, 1989). Doxycycline pharmacokinetics after PO administration were best described in this animal species by a 2-compartment open model, which is in accordance with previous studies in pigs (Baert et al, 2000), calves with immature ruminal function (van Gool et al, 1986;Meijer et al, 1993), chickens (Anadó n et al, 1994;Espigol et al, 1997;Laczay et al, 2001) and turkeys (Santos et al, 1996).…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations